Novel digital technique for measuring the volumetric healing process of free gingival grafts surrounding dental implants - Docampo-Vázquez, Cristian; Gragera-Alia, Teresa; Fernández-Domínguez, Manuel; Zubizarreta-Macho, Álvaro; Aragoneses-Lamas, Juan Manuel (Frontiers in Dental Medicine, 2024)
The objective of the present study was to analyze and describe a new digital technique for analyzing the volumetric healing process of free gingival grafts in both donor and recipient locations surrounding a dental implant, as well as to compare the reliability of conventional and digital techniques for measuring the width of the free gingival graft in the recipient location throughout the healing process. Materials and methods: Ten patients presenting with mucositis linked to a dental implant were included. A preoperative soft tissue width <2 mm, with probing pocket depth <5 mm, edema and inflammation and bleeding on probing was determined A digital impression was taken of both donor and recipient locations using an intraoral scan, generating a Standard Tessellation Language digital file both preoperatively (STL1) and after 1 week (STL2), 1 month (STL3), 3 months (STL4), and 6 months (STL5) of follow-up. Afterwards, the digital files (STL1-STL5) were aligned using a reverse engineering morphometric software, and Student’s t-test was used to analyze changes in volume at the donor and recipient locations. Additionally, widths were measured both clinically and digitally so as to compare the reliability of these measurement techniques. The repeatability and reproducibility of both these measurement techniques were also analyzed using Gage R&R statistical analysis. Results: Gage R&R found that total variability of the digital technique was 0.6% (among the measures of each operator) and 7.6% (among operators); as variability was under 10%, the results were repeatable and reproducible. In addition, there were statistically significant differences between donor and recipient locations in healing process volume (mm3) after one week (p = 0.0110), one month (p = 0.0007), three months (p < 0.0001) and six months (p = 0.0004) of follow-up. Conclusion: The digital measurement technique provided accurate, repeatable, and reproducible results when analyzing the volumetric and lineal measures of the healing process in both the donor and recipient locations of a free gingival graft surrounding a dental implant, with significantly higher tissue volume in the recipient location.